Biofouling in membrane bioreactors - Kong, Jian. (2008)
Study of the membrane biofouling problem in Membrane Bioreactor (MBR) system. Several factors that can cause the biofouling include the principle of membrane biofouling, types of biofoulants, characterization of membrane biofoulants, especially the role of extracellular polymeric substances (EPS) in MBR.